Effect of intravenous immunoglobulin administration on erythrocyte and leucocyte parameters. (28th November 2017) - Cicha, A.; Fischer, M.B.; Wesinger, A.; Haas, S.; Bauer, W.M.; Wolf, H.M.; Sauerwein, K.M.T.; Reininger, B.; Petzelbauer, P.; Pehamberger, H.; Handisurya, A.
Abstract: Background: Intravenous immunoglobulins (IVIG) are an attractive therapeutic tool for therapy of toxic epidermal necrolysis and severe forms of certain autoimmune diseases, including dermatomyositis, autoimmune blistering diseases, systemic vasculitis and lupus erythematodes. Objectives: Prompted by a case of IVIG‐associated haemolytic anaemia, the effects of IVIG administrations on haematological parameters in patients with dermatological conditions were investigated. Methods: Erythrocyte and leucocyte parameters were retrospectively analysed in 16 patients who had received IVIG at doses from 1 to 3 g/kg bodyweight ( n = 35 cycles). The influence of IVIG on leucocyte survival was determined in vitro . Results: Decreased absolute erythrocyte numbers, haemoglobin and haematocrit levels and a case of haemolytic anaemia were linked to transfusion of high‐, but not low‐dose IVIG. In contrast, leucopenia post‐IVIG occurred in the vast majority of the recipients, unrelated to the administered IVIG amounts. In vitro investigations revealed a dose‐dependent impairment of cell survival by IVIG in the neutrophil and monocyte, but not in the lymphocyte subpopulations. In several IVIG preparations, substantial amounts of blood group anti‐A/anti‐B antibodies were detected which could have accounted for the observed changes in the haematological parameters in our study cohort. Conclusions: IVIG products should be administered strictly according to indications. Commercially available IVIG products can contain blood group‐specific antibodies that may induce haemolysis in some recipients. Monitoring of blood counts during applied IVIG therapy, especially when high doses are administered, is recommended.